Surfactant-stabilized TiO2 nanofluids: Experimental investigation on thermal and viscous behavior for PV module cooling - Askar Kassymov; Ainur Adylkanova; Anuar Bektemissov; Temirlan Umyrzhan; Zhandos Akishov; Müslüm Arıcı (Heritage and Sustainable Development)
The potential application of nanofluids looks promising in various fields due to their enhanced thermal conductivity properties. The use of nanofluids in hybrid solar collectors looks particularly attractive. The thermal conductivity of the nanofluid, along with viscosity characteristics, has a significant impact on the efficiency of the solar collector. This article investigates the thermophysical properties, such as thermal conductivity and kinematic viscosity of TiO2-bidistilled water nanofluid in the presence of SDBS and CTAB surfactants at TiO2-surfactant ratios of 1:0.1, 1:0.5, 1:1 in the temperature range of 20-60 °C (293-333K). Thermal conductivity was determined using Thermtest THW-L2 equipment. Viscosity was measured using a glass capillary viscometer. The highest enhancement in thermal conductivity was observed with the SDBS surfactant, which corresponded to a lower viscosity index. At 60°C, the TiO2-bidistilled water nanofluid containing SDBS exhibited a significant thermal conductivity increase, reaching 0.690 W/(m2K). In comparison, the CTAB surfactant led to a more pronounced rise in the kinematic viscosity of the nanofluid relative to SDBS. At a 1:0.1 TiO2-to-surfactant ratio, the nanofluid stabilized with CTAB had a viscosity of 1.613 cSt at 20°C, whereas with SDBS, it measured 1.546 cSt. A regression analysis was conducted on the thermophysical data, leading to the development of descriptive models.